THE EFFECT OF SERVICE QUALITY AND INPATIENT FACILITIES ON TBC PATIENT SATISFACTION AT THE RIK UNIT OF DR. SOETOMO GENERAL HOSPITAL IN SURABAYA - Farid Tri Prasetyo (Suluh Adiluhung Publisher (SAPub), 2026)
This study aims to analyze and understand the